Opt-out bloodborne virus screening: a cross-sectional observational study in an acute medical unit - Deirbhile Keady; Niamh Allen; Collette Faherty; Andre Davies; Anne Lyons; Margarent Scarry; Mary Bohan Keane; Nicola Boyle; Sarah O’Connell; Eithne McCarthy; Colm Bergin; John Lee; et al. (BMJ Open)
Objective Recent treatment developments for HIV, hepatitis C virus (HCV) and hepatitis B virus (HBV) have greatly improved prognoses. Current screening practices are mainly risk based and are suboptimal. Improved efforts are critically needed to identify persons with these viruses. The aims of this study were to assess the feasibility of an opt-out bloodborne virus (BBV) screening programme in an acute medical unit (AMU) and to describe the prevalence of HIV, HBV and HCV in this population.Design and setting This was a cross-sectional observational study in the AMU of a tertiary referral hospital in Galway, a city in the west of Ireland.Participants 1936 patients entered the study; 54% were male, mean age was 53.1 years (SD 19.6). During the study period, all patients attending the AMU aged ≧16 years who were having bloods drawn and who had the ability to verbally consent for an additional blood sample met the inclusion criteria for the study.Results Over 44 weeks, 1936/4793 (40.4%) patients consented to BBV panel testing. Diagnosed prevalence rates for HIV, HBV and HCV were 0.5/1000, 2/1000 and 1.5/1000, respectively. There was one HIV-positive result; the patient was already engaged in care. Four patients tested positive for HBV surface antigen; one new diagnosis, one previously lost to follow-up and two already engaged in care. Three patients had active HCV infection; two had been lost to follow-up and are now linked back into services.Conclusion BBV testing uptake of 40.4% is higher than previous studies in AMU settings that used opt-in strategies, but lower than expected, possibly due to not incorporating testing into routine practice. The diagnosed prevalence of HBV is notable as little data currently exist about its prevalence in Ireland. These data are valuable in order to inform further prevention strategies for these infections in low-prevalence settings.